2022
DOI: 10.2196/27939
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Live Health Professional–Led Group eHealth Interventions for Adult Mental Health: Systematic Review of Randomized Controlled Trials

Abstract: Background The COVID-19 pandemic has had adverse impacts on mental health and substance use worldwide. Systematic reviews suggest eHealth interventions can be effective at addressing these problems. However, strong positive eHealth outcomes are often tied to the intensity of web-based therapist guidance, which has time and cost implications that can make the population scale-up of more effective interventions difficult. A way to offset cost while maintaining the intensity of therapist guidance is t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 72 publications
(283 reference statements)
0
8
0
Order By: Relevance
“…Internet-based remote interventions are playing an increasingly important role in the context of strict isolation measures as the epidemic progresses ( Heckendorf, Lehr, and Boß 2022 ; Dixon, Holoshitz, and Nossel 2016 ). Increasing evidence suggests that child and adolescent mental health network interventions have better feasibility, acceptability, and effectiveness ( Korpilahti-Leino et al 2022 ; Currie et al 2022 ). Numerous organizations have created online tools and specific interventions to help young children cope with stress and mental health issues during the pandemic ( Meherali et al 2021 ).…”
Section: Intervention or Preventionmentioning
confidence: 99%
“…Internet-based remote interventions are playing an increasingly important role in the context of strict isolation measures as the epidemic progresses ( Heckendorf, Lehr, and Boß 2022 ; Dixon, Holoshitz, and Nossel 2016 ). Increasing evidence suggests that child and adolescent mental health network interventions have better feasibility, acceptability, and effectiveness ( Korpilahti-Leino et al 2022 ; Currie et al 2022 ). Numerous organizations have created online tools and specific interventions to help young children cope with stress and mental health issues during the pandemic ( Meherali et al 2021 ).…”
Section: Intervention or Preventionmentioning
confidence: 99%
“…A possible solution is to offer therapist-led eHealth interventions in groups. If effective, group eHealth interventions could increase public access to mental health professionals during and after a pandemic [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the results should be considered with caution due to the high heterogeneity (I 2 = 93% and 95%). High heterogeneity also characterised the systematic review by Currie et al, who evaluated the effectiveness of group eHealth interventions delivered by health professionals on mental health [ 44 ]. A medium effect was noted for anxiety reduction compared to inactive interventions or active controls, as well as a medium and small effect for depression reduction compared to inactive and active controls.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was a facilitating factor for the observation of the participants´ behavior during the meetings, as well as during individual contact outside the sessions, whenever necessary. According to a systematic review (Currie et al, 2022), the group approach, with the constant presence and guidance of professionals, made the intervention less expensive for the participants while still being effective in dealing with various mental health issues. It was observed that the combination and cohesion of the clinical staff favored feelings of acceptance and commitment by the participants, enhancing their adherence and engagement with the work proposal.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review published in 2019 (Gentry et al 2019) indicated the viability of therapeutic group approaches by videoconference with similar results to in-person treatment, in addition to high participant satisfaction. Another review concluded that online group interventions conducted by healthcare professionals, can have a moderate impact on participants' anxiety (Currie et al, 2022).…”
Section: Introductionmentioning
confidence: 99%